2003
DOI: 10.1073/pnas.0935903100
|View full text |Cite
|
Sign up to set email alerts
|

Tropical rain forest tree growth and atmospheric carbon dynamics linked to interannual temperature variation during 1984–2000

Abstract: During 1984 -2000, canopy tree growth in old-growth tropical rain forest at La Selva, Costa Rica, varied >2-fold among years. The trees' annual diameter increments in this 16-yr period were negatively correlated with annual means of daily minimum temperatures. The tree growth variations also negatively covaried with the net carbon exchange of the terrestrial tropics as a whole, as inferred from nearly pole-to-pole measurements of atmospheric carbon dioxide (CO 2) interpreted by an inverse tracer-transport mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

37
423
5
12

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 472 publications
(477 citation statements)
references
References 36 publications
37
423
5
12
Order By: Relevance
“…However, as Clark et al (2003) track a single cohort of trees including only those that survive the whole monitoring period and not a dynamic population of trees, this result ought to be treated with caution. Ageing populations are to be expected to exhibit a long-term decline in net stem growth as increasing numbers of trees would reach the canopy and switch (at least some) allocation from stem growth to reproduction, and/or others would reduce growth as they senesce.…”
Section: (Iv) Temperature and Ontogenetic Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…However, as Clark et al (2003) track a single cohort of trees including only those that survive the whole monitoring period and not a dynamic population of trees, this result ought to be treated with caution. Ageing populations are to be expected to exhibit a long-term decline in net stem growth as increasing numbers of trees would reach the canopy and switch (at least some) allocation from stem growth to reproduction, and/or others would reduce growth as they senesce.…”
Section: (Iv) Temperature and Ontogenetic Developmentmentioning
confidence: 99%
“…The effect may be large, as only ca. 25% of the originally marked trees were included in the Clark et al (2003) analysis. In addition, the temperature data used are from two different sites (the first spans 1984-1991, the second 1992-2000).…”
Section: (Iv) Temperature and Ontogenetic Developmentmentioning
confidence: 99%
“…1). At each six-month time step, animals survive and breed according to probabilities observed in the long-term lion studies in the Serengeti National Park and in Ngorongoro Crater 14,15 . Demographic parameters depend on the age, sex and social status of individual lions.…”
Section: Changes In Forest Dynamics and Growthmentioning
confidence: 99%
“…In addition, lianasclimbing woody vines that often thrive in disturbed forest-appear to be increasing in size and abundance 12 . A plausible cause of these changes is increasing plant fertilization caused by rising atmospheric CO 2 concentrations [2][3][4][5][6][7][8][9][10][11][12][13] , although other large-scale phenomena, such as alterations in regional temperature 14 , rainfall 15,16 , available solar radiation 17 , or nutrient deposition 18 , might also play a role. However, no studies have assessed the effects of such large-scale changes on the taxonomic composition of Amazonian tree communities, which greatly influences the architecture, dynamics and ecological functioning of these forests.…”
mentioning
confidence: 99%
“…However, studies relating the effects of daylength and temperature on plant growth are still scarce for tropical species (Vaz et al, 2004), if one considers the plant diversity in these areas. Concerning tropical trees, a long term study of six species of an old-growth tropical rain forest relating productivity, atmospheric carbon dynamics and annual temperatures was conducted by Clark et al (2003), in Costa Rica. The authors concluded that the annual increments in tree diameter were negatively correlated with annual means of daily minimum temperatures and that net primary production covaried negatively with inferred annual net CO 2 exchange between the terrestrial tropics and the atmosphere.…”
Section: Introductionmentioning
confidence: 99%